The effect of methotrexate on blood, liver, and renal parameters in patients with rheumatoid arthritis - Bizav Rasheed; Beri Tawfeq (Medical Laboratory Journal)
Background: Rheumatoid arthritis (RA) is a long-term autoimmune disorder that primarily affects joints. The disease may also affect other parts of the body, including the skin, eyes, lungs, heart, nerves, and blood. This study aimed to evaluate the effect of methotrexate on blood, liver, and renal parameters in patients with RA. Methods: A six-month cross-sectional study was carried out on 60 consecutive patients aged 19-70 years diagnosed with RA on methotrexate treatment (10 mg) orally per week. A questionnaire was taken from participants, and laboratory tests were done on renal and liver function and complete blood count (CBC), erythrocyte sedimentation rate (ESR), glutamic oxaloacetic transaminase (SGOT or AST), glutamate pyruvate transaminase (SGPT or ALT), Creatinine, C-reactive protein (CRP), and rheumatoid factor (RF) as a follow-up to drug intake. Results: At the end of sample collection, participants ranged in age from 19 to 70 years, with a female-to-male ratio of 1.5:1. Significant differences in platelet (PLT) levels were observed only between days 1 and 14 of the treatment (p <0.05). Similarly, SGPT levels showed significant variation between days 1 and 30 of the treatment (p <0.05). Additionally, RF levels exhibited significant differences between days 1 and 14 (p <0.01) and between days 1 and 30 of the treatment (p <0.04). Conclusion: The recommended medication for all kinds of patients with RA is methotrexate, which has had a notable impact on blood, liver, and kidney parameters. These characteristics can serve as indicators for monitoring the medication’s effectiveness, safety, and patient follow-up.